Multi-sensor registration method based on a composite standard artefact. (November 2020) - Zhang, Fumin; Ge, Ruyue; Zhao, Yan; Kang, Yanhui; Wang, Zhong; Qu, Xinghua
Highlights: The method is stable and reliable. The RMSEs of the registration experiments in X and Y -directions are 6 μ m and 4 μ m, respectively. And the combined standard uncertainties are u c ( t x ) = 1.6 μ m and u c ( t y ) = 1.2 μ m . Compared with the traditional methods using the same feature, it is able to avoid the situation that different sensors may not measure the same feature points. Compared with other methods, the process is greatly simplified and the accuracy is improved. Abstract: Registration is a critical and essential procedure in any multi-sensor dimensional measuring systems. Most of the traditional registration methods are achieved by measuring a common standard by multiple sensors; however, it is difficult to ensure that heterogeneous sensors measure the same feature points. In this study, a new multi-sensor registration method based on a composite standard artefact is proposed. The base of the standard artefact is equipped with a standard sphere and a standard chrome-circle for registering the visual sensor (VS) and the tactile probe sensor (TPS) on a multi-sensor dimensional measuring machine. The VS and TPS measure the standard chrome-circle and the standard sphere, respectively. The coordinate system conversion parameters between the two sensors were solved based on the constant distance between the standard chrome-circle centre and the standard sphere centre. Both the simulations and experiments demonstrate higher precision and stability of the proposed method for the registration of multiple heterogeneous sensors in high-precision dimensional measurement systems. The root mean square errors of the registration experiments in X and Y -directions are 6 μ m and 4 μ m, respectively. The combined standard uncertainties are u c ( t x ) = 1.6 μ m and u c ( t y ) = 1.2 μ m .